Dżihad w praktyce : Asyryjczycy miejscowości Azach (Azakh) w Górnej Mezopotamii w latach I wojny światowej : opór, ugoda, zdemilitaryzowanie, exodus - Abdalla, Michael (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
Among thousands of Assyrian towns located until WWI in present-day southeastern Turkey, the article briefly presents the long history of one selected village by the name of Azakh, and tells the tragedy that befell its inhabitants
Keywords: Azach (Azakh); Asyryjczycy; Kurdowie; Turcja; wojna światowa (1914-1918); exodus